Síntese de óxidos alternativos para células a combustível de óxido sólido de temperatura intermediária - Souza, Graziele Lopes de (2017)
Solid oxide fuel cells are the most efficient devices ever invented for the conversion of chemical fuels directly into electrical energy. These devices still have the disadvantage of operating at relatively high temperature. La2-xNiO4+d cathode, series materials with structure K2NiF4, have been considered as very promising materials due to their high mixed ionic electronic to intermediate temperature. The interest in these oxides as functional material for cathode increased because of its oxygen permeability and its stability. This material has coefficient of thermal expansion compatible with electrolytes from the La10-x(SiO4)6O2+-d family and apatite structure. These electrolytes have higher conductivities than zirconia-based electrolytes if used in the same temperature range as the above-mentioned cathode. This work reports the synthesis of apatite-type lanthanum silicate powders with nominal composition La10Si6O27 and Lanthanum nickelate (La2NiO4) for using as electrolyte and cathode materials, respectively, in solid oxide fuel cells. The lanthanum silicate was obtained from a co-precipitation chemical route, while the cathode was obtained by the citrate method. The herein proposed synthetic procedure is advantageous in reducing energy consumption and processing time, key elements to decrease the total manufacturing cost. At the end of the syntheses, the precursors powders were characterized by thermogravimetric analysis. The lanthanum silicate powders as prepared were calcined between 500 and 900 °C and characterized by X-ray diffraction (XRD), Rietveld refinement and scanning electron microscopy (SEM). Already the lanthanum nickelate was calcined in a single temperature 1200 °C for 4h and characterized by SEM. The structural characterization of the electrolyte indicated the formation of biphasic material after calcination at 900 °C. The effect of sintering temperature, ranging from 1400 to 1450 °C, on the electrical properties was investigated by impedance spectroscopy. Electrical measurements were recorded in the 400 – 800 °C temperature range in air. The lanthanum silicate electrolyte sintered at 1450 °C exhibited total electrical conductivity 2.12 x 10-3 S.cm-1 in 700 °C comparable with samples from literature prepared and sintered at 1500 °C. The electrochemical performance as cathode material was evaluated in a symmetrical cell configuration (cathode/substrate/cathode) using the electrochemical impedance spectroscopy. Lanthanum nickelate cathodes obtained by screen printing and sintered at 1300 ° C for 4 h had an area specific resistance (ASR) of 2.85 ohm.cm2 at 800 ° C under oxygen atmosphere. Lanthanum nickelate was mixed with the electrolyte material and sintered at the same temperature used to sinter the cathode film, in order to evaluate possible chemical reactions between them. The materials showed good electrochemical results compared to the literature and chemical stability up to 1300 ° C.